Optical properties of cerium oxide doped zinc borotellurite glass / Hasnimulyati Laoding, Halimah Mohamed Kamari, Azuraida Amat, Azianty Saroni - Laoding, Hasnimulyati; Mohamed Kamari, Halimah; Amat, Azuraida; Saroni, Azianty (Universiti Teknologi MARA Shah Alam, 2023)
The addition of rare earth, zinc, and borate in tellurite glass was found can enhance the glass properties and overcome its existing weaknesses. These include improving the glass forming ability and stability. In this study, cerium-doped zinc borotellurite glasses were produced using conventional melt-quenching technique and the optical properties of the glasses were investigated. UV-VIS spectra show that the absorption edge shifted to a higher wavelength with CeO2 addition from 0 until 0.05 mol. Consequently, the direct and indirect optical band gap was found to decrease from 3.60 to 2.07 eV and 3.28 to 1.46 eV respectively. On the contrary, the refractive index was found to increase from 2.326 to 3.017. This is attributed to the presence of cerium ions and the formation of non-bridging oxygens. Besides that, the Urbach energy found to be maximum at 0.02 mol CeO2 and minimum at 0.00 mol CeO2. This indicates that there are some structural disorders occur in the glass network as CeO2 introduced into the system. The molar refraction, molar polarizability, oxide ion polarizability and optical basicity exhibited similar trend of data as the CeO2 content was increased which signifies the relation of these parameters. Meanwhile, the metallization criterion is reported to be decreased, indicating that the glass sample become more metallized with the addition of cerium oxide.